Motosify: Aplikasi Diagnosis dan Penyelenggaraan Motosikal - Azhar, Amirul Afiq; Ab. Aziz, Mohamad Firdaus (Applied Information Technology And Computer Science, 2021)
Motosify application is developed to helps new motorcycle riders and experienced riders to diagnose and service their motorcycles. Most of the new motorcycle riders did not have the required knowledge for diagnosis and basic maintenance routine. Thus, unresponsible motorcycle repair shops can easily takes advantage of them. This can be in the form of using a knock off parts to repair the customer’s motorcycle and lying to the customers about the service that has been done to the motorcycle. This can damage the customer’s motorcycle. Next, the diagnosis process that is done by mechanic can take a long time and as a result, the customer have to wait long for the process. The long diagnosis process is to make sure that the problem can be diagnosed correctly. In addition, existing application did not have ample information. Based on the several problems listed, the Motosify application is developed. This application is developed using Android Studio software. The programming language that is used during development is java programming language. For the interface design, Adobe Photoshop was used. This application is designed with the minimalist design theme which is the same as the current design trend for application. The database that is used to store data in this application is the Firebase Database that is come packaged in Android Studio. The development of this application follows the agile methodology workflow. The user for this application is new motorcycle riders and experienced motorcycle riders. This application can diagnose user’s motorcycle problem. Besides that, it can also display nearby workshop location based on the user’s current location. Lastly, this application records all user’s activity when they use any features of the application.